2015
DOI: 10.1080/11250003.2015.1060268
|View full text |Cite
|
Sign up to set email alerts
|

Transfer of egg white proteins with reference to lysozyme during the development ofMeleagris gallopavo(Galliformes: Phasianidae) embryos

Abstract: The egg white and egg yolk are the two main sources of nutrients for the developing avian embryo. The egg white should be transferred into the yolk in order to be consumed by the embryo. How the egg white ultimately reaches the egg yolk is largely unexplored in the turkey Meleagris gallopavo. Here, we explored the routes of egg white transfer in fertilized turkey eggs. Initially, we tested the electrophoretic pattern of the proteins in different egg compartments throughout development. Then, we used lysozyme a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
21
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(26 citation statements)
references
References 38 publications
5
21
0
Order By: Relevance
“…Although the reduction of the mRNA expression preceded that of the protein activity, a sufficient protein level was apparently present to maintain the enzymatic activity. We previously showed that three large electrophoretic protein bands disappeared while a small one appeared in the developmental period between days 24 and 26, which further supports the presence of proteolytic activity during this period (Shbailat & Safi 2015). Given that the amniotic fluid almost disappears from the intestinal lumen after day 26 (de Oliveira et al 2009;Shbailat & Safi 2015), it is possible that the egg white proteins and all their digested products are transferred from the intestinal lumen into the yolk together with all the secreted proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…Although the reduction of the mRNA expression preceded that of the protein activity, a sufficient protein level was apparently present to maintain the enzymatic activity. We previously showed that three large electrophoretic protein bands disappeared while a small one appeared in the developmental period between days 24 and 26, which further supports the presence of proteolytic activity during this period (Shbailat & Safi 2015). Given that the amniotic fluid almost disappears from the intestinal lumen after day 26 (de Oliveira et al 2009;Shbailat & Safi 2015), it is possible that the egg white proteins and all their digested products are transferred from the intestinal lumen into the yolk together with all the secreted proteolytic enzymes.…”
Section: Discussionmentioning
confidence: 88%
“…to the obvious transfer of egg white proteins into the yolk (Shbailat & Safi 2015). Previously, we found that one small electrophoretic band (19.6 KDa) appeared at late developmental stages in the egg yolk, while a relatively large one (36.5 KDa) disappeared 1 day after hatching (Shbailat & Safi 2015). Therefore, we suggested the presence of proteolytic activity that caused the digestion of egg yolk proteins.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations